Perpustakaan Laman Hikmah menyemarak budaya membaca di Universiti Teknikal Malaysia Melaka (UTeM) - ABU BAKAR, RASIDA (Perpustakaan Negara Malaysia, 2022)
The reading campaign in Malaysia which officially started in 1995 with the aim of creating a knowledgeable and informed society. An effective reading culture has not yet reached an encouraging level among UTeM residents. Laman Hikmah Library plays an important role in nurturing and invigorating the reading culture campaign with various activities related reading to support the National Reading Decade and Read@Uni campaigns. This study uses a qualitative method that includes aspects of observation, document analysis, brief review, views and interviews in PLH. Challenges and suggestions for improvement in preserving the reading culture are also focused. The culture of reading at UTeM needs to be significant and change into the main pulse for students and academic staff in order to achieve the dignity of scholarship and intellectualism as a habit and lifelong learning.